Assessment of the Thermal Comfort Conditions in a University Campus Using a 3D Microscale Climate Model, Utilizing Mobile Measurements - Nastos, P. T.; Moustris, K. P.; Charalampopoulos, I.; Larissi, I. K.; Paliatsos, Athanasios G (PERSPECTIVES ON ATMOSPHERIC SCIENCES, 2016)
The objective of the study is to assess the human thermal comfort at a University Campus in the metropolitan area of Athens. The equipment setup consists of all the necessary sensors for human thermal comfort estimation along with a high resolution GPS, mounted on a cargo bicycle. The experiment was carried out for midday and night on July 29, 2015. Besides, long term 5 min measurements from a meteorological station, established on the roof of a building within the University Campus, were also used to quantify the mean thermal environment. The densely carried out bicycle measurements every 5 s was the input data utilized by the ENVI-met model; a three-dimensional microclimate model designed to simulate the surface-plant-air interactions in urban environment. The in situ measurements along with the model's output results reveal the thermal comfort regime of the selected area and the ability of the model to estimate accurately the micrometeorological conditions.